2005
DOI: 10.1128/jvi.79.14.9097-9107.2005
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of SH1, a Novel Lipid-Containing Virus Infecting the Halophilic Euryarchaeon Haloarcula hispanica

Abstract: Recent studies have indicated that a number of bacterial and eukaryotic viruses that share a common architectural principle are related, leading to the proposal of an early common ancestor. A prediction of this model would be the discovery of similar viruses that infect archaeal hosts. Our main interest lies in icosahedral double-stranded DNA (dsDNA) viruses with an internal membrane, and we now extend our studies to include viruses infecting archaeal hosts. While the number of sequenced archaeal viruses is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(135 citation statements)
references
References 73 publications
3
129
1
Order By: Relevance
“…This is likely because physico-chemical variables in the oceanic samples did not approach the 'extreme' conditions from which these exceptional morphotypes have been isolated. However, there are non-marine archaeal viral isolates with icosahedral non-tailed morphology (Bamford et al, 2005;Atanasova et al, 2012;Jaakkola et al, 2012) and further exploration of marine archaeal virushost systems may yield more examples.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely because physico-chemical variables in the oceanic samples did not approach the 'extreme' conditions from which these exceptional morphotypes have been isolated. However, there are non-marine archaeal viral isolates with icosahedral non-tailed morphology (Bamford et al, 2005;Atanasova et al, 2012;Jaakkola et al, 2012) and further exploration of marine archaeal virushost systems may yield more examples.…”
Section: Discussionmentioning
confidence: 99%
“…Flow rate was 50µl/min and detection at 214nm. For in-gel digestion the P16 and P17 protein bands from SDS-PAGE (Laemmli 1970) were separately in-gel digested with trypsin (Bamford et al 2005) and the resulting peptides subjected to peptide mass fingerprint analysis by MALDI-TOF mass spectrometry.…”
Section: Inhibin B Elisa Assaymentioning
confidence: 99%
“…It has an icosahedral capsid with spikes on the five-fold vertices, an inner lipid membrane, and no tail. The linear dsDNA genome has inverted terminal repeats and proteins attached to the termini [7,43]. However, closer analysis of the 31-kb genome and the capsid structure revealed that SH1 differs markedly from members of the Tectiviridae.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, a spherical halovirus, SH1, infecting the euryarchaeon Haloarcula hispanica was isolated from Lake Serpentine in Western Australia [13] and characterized in detail during the next few years [7,23,29,[42][43][44]. The particle morphology and genome structure of this virus resemble those of bacteriophages belonging to the family Tectiviridae [2].…”
Section: Introductionmentioning
confidence: 99%